Stryke i praksis - er det mulig? Sykepleiestudenters opplevelse av å få ikke-bestått i praksisstudier - Hauge, Kari Westad (Nordisk tidsskrift for helseforskning, 2015)
Fail practice – is that possible? Background: Research describes that supervisors are put in predicament when having to fail a student nurse. There is a lack of research related to the experience of failing to student. Purpose: The purpose of the study is to describe how student nurse experience to fail practice and the process that lead to this outcome. Method: A qualitative interview with a phenomenological and hermeneutic approach. Results: Failing practice trigger strong feelings and reactions by the students. These enhance if they don’t understand the reason for failing, experience the process as unfair or if they don’t get the necessary guidance, feedback and support in the situation. Conclusion: To preserve the dignity and vision of future possibility of a failing student, the supervisors and teachers relational competence and willingness to see the student is important.